Challenges for Managing Fisheries on Diverse Coral Reefs - Douglas Fenner (Diversity, 2012)
Widespread coral reef decline has included the decline of reef fish populations, and the subsistence and artisanal fisheries that depend on them. Overfishing and destructive fishing have been identified as the greatest local threats to coral reefs, but the greatest future threats are acidification and increases in mass coral bleaching caused by global warming. Some reefs have shifted from dominance by corals to macroalgae, in what are called “phase shifts”. Depletion of herbivores including fishes has been identified as a contributor to such phase shifts, though nutrients are also involved in complex interactions with herbivory and competition. The depletion of herbivorous fishes implies a reduction of the resilience of coral reefs to the looming threat of mass coral mortality from bleaching, since mass coral deaths are likely to be followed by mass macroalgal blooms on the newly exposed dead substrates. Conventional stock assessment of each fish species would be the preferred option for understanding the status of the reef fishes, but this is far too expensive to be practical because of the high diversity of the fishery and poverty where most reefs are located. In addition, stock assessment models and fisheries in general assume density dependent populations, but a key prediction that stocks recover from fishing is not always confirmed. Catch Per Unit Effort (CPUE) has far too many weaknesses to be a useful method. The ratio of catch to stock and the proportion of catch that is mature depend on fish catch data, and are heavily biased toward stocks that are in good condition and incapable of finding species that are in the worst condition. Near-pristine reefs give us a reality check about just how much we have lost. Common fisheries management tools that control effort or catch are often prohibitively difficult to enforce for most coral reefs except in developed countries. Ecosystem-based management requires management of impacts of fishing on the ecosystem, but also vice versa. Marine Protected Areas (MPAs) have been a favorite management tool, since they require little information. MPAs are excellent conservation and precautionary tools, but address only fishing threats, and may be modest fisheries management tools, which are often chosen because they appear to be the only feasible alternative. “Dataless management” is based on qualitative information from traditional ecological knowledge and/or science, is sufficient for successful reef fisheries management, and is very inexpensive and practical, but requires either customary marine tenure or strong governmental leadership. Customary marine tenure has high social acceptance and compliance and may work fairly well for fisheries management and conservation where it is still strong.